2017
DOI: 10.1016/j.apt.2016.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Soybean oil methanolysis over scallop shell-derived CaO prepared via methanol-assisted dry nano-grinding

Abstract: Calcium oxides with a specific surface area between 4.5 m 2 g-1 and 62.5 m 2 g-1 were obtained by calcination of scallop shells, following by methanol-assisted dry nano-grinding. Three distinct phases are formed on the surface of these catalysts during nano-grinding: calcium methoxide, calcium hydroxide, and calcium oxide. The effects of specific surface area and active surface phase composition on the catalytic activity of calcium oxide during methanolysis of soybean oil were investigated. The properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…The D 50 values are 11.27 µm, 21.148 µm, and 42.65 µm acetone-assisted, ethanol-assisted and dry state methods, respectively. This phenomenon was in agreement with Panjaitan et al (2016), by the SEM analysis, revealed agglomeration occurring during the grinding course [8]. The reason for distinguished D 50 results on applying solvent-assisted was the interaction of solvents (ethanol or acetone) which partially coat the MCC during the grinding, thus prevents the agglomeration.…”
Section: Distribution Of Particle Sizesupporting
confidence: 74%
See 2 more Smart Citations
“…The D 50 values are 11.27 µm, 21.148 µm, and 42.65 µm acetone-assisted, ethanol-assisted and dry state methods, respectively. This phenomenon was in agreement with Panjaitan et al (2016), by the SEM analysis, revealed agglomeration occurring during the grinding course [8]. The reason for distinguished D 50 results on applying solvent-assisted was the interaction of solvents (ethanol or acetone) which partially coat the MCC during the grinding, thus prevents the agglomeration.…”
Section: Distribution Of Particle Sizesupporting
confidence: 74%
“…This phenomenon changes the crystalline structure, induces the crystal defect and dislocation. At the same time, the grinding reduces the particle size and increases the specific surface area [4,8]. Using solvent-assisted method, coarse particles of MCC become finer (Figure 2 and 3).…”
Section: Distribution Of Particle Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The synthesized catalyst was used to assist the methanolysis reaction between refined Jatropha curcas oil containing extremely low FFAs content. Additionally, the catalytic activity of CaDg have been tested for biodiesel production from few lipid feedstocks such as, soybean oil [21,26,27], sunflower oil [28], castor oil [29] and waste cooking oil [30]. Looking at the novel catalytic proficiency of glycerol-enriched CaO, the reports focused on its utilization for biodiesel production are extremely low in comparison with those of neat CaO catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…where TLj is the total loss function, Wi is the number of response variable, and ηj is SNR value [28][29].…”
Section: Experimental Designmentioning
confidence: 99%